Relationship between functional independence and psychosocial quality of life of stroke survivors undergoing outpatient rehabilitation in Maiduguri, Nigeria - Grace Vincent-Onabajo; Nyangwae Daniel Shaphant (SpringerOpen, 2019)
Abstract Background There are divergent findings on the impact of functional independence on psychosocial quality of life (QoL) of stroke survivors. Aim To investigate the relationship between functional independence and psychosocial QoL among stroke survivors in Maiduguri, Nigeria. Methods A cross-sectional design was utilized, and functional independence and psychosocial QoL of consecutive stroke survivors undergoing rehabilitation were assessed with the motor subscale of the Functional Independence Measure (motor- FIM) and the psychosocial subscale of the Stroke-Specific Quality of Life Scale-12 (SS-QoL- 12) respectively. Relationships between the two variables were explored with Pearson's correlation coefficients and multivariable regression analysis. Results Fifty-nine stroke survivors participated in the study with a male majority (54.2%). Correlation between motor-FIM and the psychosocial subscale scores was not statistically significant (r = 0.24; p = 0.07) while correlation between motor-FIM and each item of the psychosocial subscale showed that a statistically significant correlation (r = 0.29; p = 0.02) was present for the 'mood' item only. Functional independence however did not statistically contribute to the multivariable regression model (R2 = 0.22; P < 0.01) for the 'mood' item after controlling for the effect of the participants' age and sex. Conclusion Functional independence had no independent or statistically significant relationship with overall psychosocial QoL. Further studies are therefore needed to explore modifiable factors that influence psychosocial QoL of stroke survivors in our setting.